2019
DOI: 10.1186/s12931-019-1083-1
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 induced apoptosis of type II pneumocytes during ARDS

Abstract: Objective The mechanisms of lung injury in acute respiratory distress syndrome (ARDS) are not well understood.Piezo1 was recently identified as a mechanotransduction protein. The present study found the expression of Piezo1 in type II pneumocytes and investigated its role in mediating ARDS-related lung injury. Methods Sprague-Dawley rats were used to establish an ARDS model, the expression of Piezo1,lung injuries, apoptosis as well as calcium influx were assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
(32 reference statements)
3
24
0
Order By: Relevance
“…2f) 23,24 . This mechanism is further supported by previous studies that show Piezo1 activation leads to the downregulation of Bcl-2 and upregulation of calpain activity 21,39 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2f) 23,24 . This mechanism is further supported by previous studies that show Piezo1 activation leads to the downregulation of Bcl-2 and upregulation of calpain activity 21,39 .…”
Section: Discussionsupporting
confidence: 83%
“…One potential explanation for this shear stress mechanism is the activation of mechanosensitive ion channels (MSCs), specifically the MSC Piezo1. Piezo1 is an MSC that opens in response to mechanical stimuli, such as shear stress and like other MSCs has been previously associated with proapoptotic effects 1721 . Furthermore, Piezo1 has a small molecule agonist known as Yoda1, meaning Piezo1’s activity can be translated to static conditons 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The lung tissue epithelium and the surrounding tissues undergo mechanical stretch generated by air under physiological conditions and mechanical ventilation [ 143 ]. A recent study [ 144 ] demonstrated that the Piezo1 channel was highly expressed in alveolar epithelial type ii cells (AECs), a component of the alveolar epithelium. Over-inflated alveolae caused by mechanical stretch during mechanical ventilation activated the Piezo1 channel, resulting in Ca2 + influx.…”
Section: Function Of Piezo Channelsmentioning
confidence: 99%
“…Over-inflated alveolae caused by mechanical stretch during mechanical ventilation activated the Piezo1 channel, resulting in Ca2 + influx. Subsequently, the elevated intracellular Ca2 + signal led to the apoptosis of AECs, probably through the Bcl-2 pathway [ 144 ] (Fig. 11 B).…”
Section: Function Of Piezo Channelsmentioning
confidence: 99%
“…: 1B7G5). The immunohistochemistry of lung was performed as previously reported 51 . In brief, the lung was paraffin embedded and dewaxed, then citrate buffer was used for antigen unmasking.…”
Section: Methodsmentioning
confidence: 99%